Tata Kelola Pemerintahan Berbasis Electronic Government pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Mahakam Ulu - Surya, Iman; Remon, Yusi; Angun, Indira Reisia; Yuliana, Yuliana; Himang, Willibrordus (HK-Publishing, 2024)
AbstractMahakam Ulu is a new Regency that was established independently in 2012 apart from West Kutai Regency. This research aims to determine the impact of technology in government agencies which is a challenge that must be overcome by Mahakam Ulu Regency in implementing Electronic Government in the Personnel and Human Resources Development Agency. The need for the use of e-Gov itself has developed from year to year, the Mahakam Ulu Regency government is required to be able to work hard and be proactive in dealing with current developments with the use of modern technology. This research method uses qualitative research, which is research that describes all research events that occur in the field using literature studies. The research results show that the implementation of e-Gov cannot still be said to be optimal because it is still experiencing delays in adapting to the existing technological conditions at BKPSDM Mahakam Ulu Regency: First, employee performance is always increasing, but on a digital document basis, report documents are still often delayed. Second, human resource factors (disposition) or government officials still have difficulty absorbing updated information related to the implementation of e-Gov, so special guidance is needed to be able to survive with the aim of good governance.Keywords: Government Governance, Electronic GovernmentÂ AbstrakMahakam Ulu merupakan Kabupaten baru yang berdiri sendiri pada tahun 2012 terlepas dari Kabupaten Kutai Barat. Penelitian ini bertujuan mengetahui dampak teknologi di instansi pemerintahan menjadi tantangan yang harus di lalu oleh Kabupten Mahakam Ulu dalam penerapan Electronic Government di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia. Kebutuhan penggunaan e-Gov sendiri mengalami perkembangan dari tahun ke tahun, pemerintah Kabupetan Mahakam Ulu di tuntut untuk bisa berkerja keras dan proaktif dalam menangani perkembangan zaman dengan penggunaan teknologi modern. Metode Penelitian ini menggunakan penelitian kualiatatif merupakan penelitian yang mempaparkan segala peristiwa penelitian yang terjadi di lapangan dengan batuan studi literature. Hasil Penelitian menunjukkan penerpan e-Gov masih belum bisa dikatakan optimal karena masih mengalami keterlambatan penyesuaian dengan kondisi teknologi yang ada di BKPSDM Kabupaten Mahakam Ulu : Pertama, Kinerja pegawai selalu mengalami peningkatan tetapi secara basis digital document masih sering mengalami keterlambatan dokumen laporan. Kedua, Faktor sumber daya manusia (disposisi) ataupun aparat pemerintahnya masih kesulitan menyerap informasi pembaruan terkait penerapan e-Gov sehingga diperlukan bimbingan khusus agar bisa survice dengan tujuan good governece.Kata kunci: Tata Kelola Pemerintahan, Electronic Government